The osmotic response capacity of the Antarctic fish Harpagifer antarcticus is insufficient to cope with projected temperature and salinity under climate change. (February 2021) - Vargas-Chacoff, L.; Martínez, D.; Oyarzún-Salazar, R.; Paschke, K.; Navarro, J.M.
Abstract: Over the last decades, climate change has intensified. Temperatures have increased and seawater has become "fresher" in Antarctica, affecting fish such as Harpagifer antarcticus . Thus, this study aimed to evaluate changes in the osmoregulatory response of the Antarctic notothenioid fish Harpagifer antarcticus and evaluate how it will cope with the future climate change and environmental conditions in the Antarctic, and in the hypothetical case that its geographical distribution will be extended to the Magellanes region. The present study was undertaken to determine the interaction between temperature and salinity tolerance (2 °C and 33 psu as the control group, the experimental groups were 5, 8, and 11 °C and 28 and 23 psu) and their effect on the osmoregulatory status of H. antarcticus . We evaluated changes in gill-kidney-intestine NKA activity, gene expression of NKAα, NKCC, CFTR, Aquaporins 1 and 8 in the same tissues, muscle water percentage, and plasma osmolality to evaluate osmoregulatory responses. Plasma osmolality decreased with high temperature, also the gill-kidney-intestine NKA activity, gene expression of NKA α, NKCC, CFTR, Aquaporins 1, and 8 were modified by temperature and salinity. We demonstrated that H. antarcticus can not live in the Magallanes region, due to its incapacity to put up with temperatures over 5 °C and with over 8 °C being catastrophic. Highlights: Potentially the new scenario of climate change is affecting the osmotic responses in fish. The plasma osmolality decreased in Harpagifer antarcticus by temperature more than salinity. The gill-kidney-intestine NKA activity were modified by salinity and temperature. H. antarcticus show incapacity to put up with temperatures over 5 °C, and with over 8 °C being catastrophic.